Textual network in Sevim Burak:|The nonhuman beings of Ford Mach I - Kutup, Selver Sezen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis proposes to consider Sevim Burak’s Ford Mach I as a textual network or a network-text. The collective creation process of Ford Mach I is one of the elements that make a textual network possible. There are multiple authors/multiple texts incorporated into Ford Mach I. The collective process does not only pertain to the writing part, but the reader is also an integral element of the network. Each reader is able to dismantle this unfinished, “open” text only to montage it afterwards. A nonhuman being, that is the automobile, is put at the center of Ford Mach I. The way this network is organized providing a heterogeneous coexistence, is parallel to Deleuze&Guattari’s conception of assemblage. Assemblage does not represent anything apart from the arrangement of elements. Accordingly, nonhuman beings are not a symbol or metaphor, and they are not owned by humans. Guided by Actor Network Theory, we can follow Ford Mach I as a text that opens up space for the agency of nonhuman beings with their potential to transform every interaction, as well as the text itself. In this way, humans, nonhumans and their agencies are in mutual entanglement within the network of Ford Mach I.